Imagology-Based Ulama Narratives in the Development of Children’s Storybooks on Islamic Economics - Firza Agung Prakoso; Tristan Rokhmawan; Reviandy Azhar Ramdhani; Ahmad Faqih Abdillah; Dahliana Kamener (Bulletin of Pedagogical Research, 2026)
The city of Pasuruan possesses a rich heritage of local ulama narratives preserved in the collective memory of the community that reflect the practice of Islamic economics in everyday life. Nevertheless, these narratives have not yet been systematically utilized as literacy media for children. This study aims to examine the representation of Islamic economic imagology in the narratives of local ulama in Pasuruan, to develop these narratives into illustrated children’s storybooks, and to analyze the acceptability of the books as Islamic economic literacy media for children. The study employs a qualitative descriptive approach using narrative and imagological analysis, followed by the development of an illustrated storybook product. The acceptability test was conducted through questionnaires administered to children as the primary readers, supported by evaluations from parents, teachers, and learning facilitators. The findings indicate that local ulama narratives construct exemplary images of role models who represent Islamic economic values in a contextual and grounded manner. The imagological approach allows ulama to be presented as inspirational figures closely connected to children’s realities, enabling Islamic economic values to be internalized through storytelling experiences. The developed illustrated storybooks demonstrate a high level of acceptability in terms of content comprehension, language, illustration, and value messaging. This study contributes to the development of a narrative-based model of Islamic economic literacy for children through the integration of imagology, storytelling, and local wisdom as an alternative, engaging, and educational value-learning approach.